The Integration of Information and Communication Technology Into Classroom Teaching - Reid, Scott (Alberta Journal of Educational Research, 2002)
This study provides new images of teachers who are pioneers in the use of information and communication technology (ICT) in the classes they teach. This qualitative study looks at teachers in a high school that is a leader in using information technology in the classroom. The findings indicate that most of the teachers participating in this study were enthusiastic about the possibilities ICT holds for classroom use. Examples are given to illustrate how information technology is being used in this school to enhance classroom teaching in several subject areas. Concerns teachers have about the use of technology were identified as issues that could determine the success or failure of the use of ICT in high schools. These concerns include: maintenance, inequalities, the need for training, information overload, the pace of change and stress, plagiarism, business involvement, and teachers' time.